Eddy-Induced Ekman Pumping in the Vitória-Trindade Ridge Region - Farias, Igor Uchoa (2019)
The transport of rich-nutrient waters to the euphotic zone is a key process in controlling primary production in the ocean. One of the most important features that are related to the boosting/damping rates of chlorophyll A in the upper ocean are eddies due to its isoypicnal displacements adjustments. In this present study, we investigated the input of eddy-induced Ekman pumping in the density structure of two main mesoscale eddies in the Vitória-Trindade vicinity: Abrolhos Eddy (anticyclonic) and Vitória Eddy (cyclonic). Using an air bulk formula for wind stress that accounts for ocean current feedback, eddy-induced Ekman pumping may be described as the sum of two terms: linear Ekman pumping (Eddy-Wind Interaction) and non-linear Ekman pumping. A three-stage analysis was conducted consisting of (i) statistical characterization of the mesoscale eddies, (ii) idealized parametrization of Ekman pumping using a homogeneous wind field, and (iii) inferences on eddy-induced Ekman pumping in mesoscale eddies isopycnal displacements. Climatological eddy structures indicated total Ekman pumping values higher than 0.1 m day-¹ for Abrolhos Eddy and lower than -0.1 m day-¹ for Vitória Eddy at the eddy center, though those values may decreased if averaged in an azimuthal sense. Isopycnal displacements seem to be correlated with the horizontal distribution of both components of Ekman pumping. Abrolhos Eddy showed a mode-water configuration related to Eddy-Wind Interaction. Vitória Eddy showed a thinny structure that seemed to be related to non-linear Ekman pumping values, yielding -1 m day-¹ with similar variation and magnitude to the vertical velocities of the eddy structure.